PENGARUH MINYAK KELAPA MURNI DAN MINYAK INTI SAWIT TERHADAP PERTUMBUHAN RAMBUT PADA KELINCI - Ritonga, Ahmad Hafizullah; Suryani, Monica; Surbakti, Christica Ilsana; Hadi, Novia Silvana (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Hair is something that comes out of the skin and has a shape like a thin thread. Hair has many things, including protection from the sun's function, adding beauty and color lines to the face, protecting the eyes from sweat, dirt and dust, and others. Hair is composed of a protein substance called keratin. To determine the VCO and PKO in the rate of growth activity and hair distribution rate. Extraction of PKO from palm kernel and VCO from the coconut fruit, characterization testing including fatty acids and squalene using the Gas Chromatography (GC) method, free fatty acids using the titration method with 0.01N KOH, and finally vitamin E using the Ultra Performance Liquid Chromatography (UPLC) method. smeared every 2 times a day. Tests for the distribution rate of hair growth and daily hair growth rate were carried out every 5th, 10th, 15th, 20th, 25th, 30th day. And weight considerations were made on the 30th day. compared to Pure Coconut Oil in hair growth in rabbits.